Animals in Stone Indian Mammals Sculptured Through Time - van der Geer, Alexandra (Brill, 2008)
The art history of South Asia covers a time span of roughly four and a half thousand years. During this period, a vast number of animal stone sculptures has been produced, ranging from the pre-historic period till today and covering a great variety of motifs and imagery in different regions and religious traditions. Even so, the number of studies devoted to these animal sculptures has remained extremely limited. The present book aims at filling this knowledge gap. With this richly illustrated book, the first of its kind, Van der Geer offers a comparative study of the ways in which various animals have been depicted and a lucid analysis of the sculptors' treatment of their "models": living animals. The art history of sculptured animals is contextualized with a description of the use of animals as can be read from ancient texts, archaeological evidence and contemporaneous culture. In doing so, parallels as well as differences in style or iconography are highlighted, elucidating the variety of animal depictions across regions, religious contexts and through time. The corpus of discussed material ranges from Indus seals, stupa panels and railings, monumental temples from North and South India, non-religious palace and fort architecture to loose sculptures in museum collections.